La Chimica a Palermo nel XVIII secolo - Zingales, Roberto (Chimica nella Scuola, 2022)
Despite the peripheral position of the city, the new Lavoisier’s chemical theory was taught also in Palermo within few years, thanks to the foresight of local Rulers, and to the thorough and painstaking work of Giovanni Meli (Professor at the Accademia). By renouncing to his phlogistic education, Meli was able to accept it and teach it to his students. On the contrary, in the 18th century, in the practical field of waters analysis, despite some deliberated attempts to apply the most common qualitative tests, ignorance and lack of the most elementary chemical skills were still predominant.